On one generalization of the averaging method - Valeyev, K. G.; Dzhalladova, I. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We consider one case where it is possible to establish sufficient conditions for the convergence and analyticity of matrix series used for the construction of a system of moment equations.